Development of an Archery Technique Test Instrument: Objective Evaluation to Improve Athlete Performance - Rofa Ichsandi; Riko Adi Baskoro; Agung Hadi Saputro; Muhammad Nur Aziz Andriawan (Universitas Negeri Semarang, 2025)
This study aims to develop a valid and reliable archery technique test instrument for recurve bow athletes to address the limitations of existing instruments, which tend to be subjective and focus solely on accuracy. The research and development (R&D) method, adapted from the steps of Borg and Gall, involved 14 athletes at the National Potential Young Athlete Training Center (SLOMPN) as the total sample. The developed test instrument not only measures accuracy (through qualification and elimination scores), but also specifically and objectively measures speed, strength, and endurance specific to the sport of archery. The seven main test components produced include: qualification score, elimination score, shooting speed, bow draw maximum quantity, bow training, battery test archery, and maximum shooting. The trial results showed that all seven test items were internally valid, with a correlation coefficient (r) higher than (rtable = 0.532). Furthermore, this instrument has a very high level of reliability (stability across testing sessions), with a test-retest correlation coefficient of 0.893. This study concludes that the developed archery technique test instrument is proven to be feasible, valid, and highly reliable for use. This instrument provides a comprehensive, objective evaluation tool, enabling coaches to profile athletes and design more effective and specific training programs, considering aspects of strength, speed, and endurance, in addition to shooting accuracy.